The Current Thoracoscopic Management of Esophageal Atresia - Fraser, Jason D.; St Peter, Shawn D. (European Journal of Pediatric Surgery, 2020)
The thoracoscopic repair of esophageal atresia with tracheoesophageal fistula is a complex neonatal minimally invasive procedure. The thoracoscopic approach is now nearing its third decade of experience and but is overall still not widely utilized, only in skilled centers and by experienced surgeons. This article will summarize the recent advancements in technique and knowledge in the thoracoscopic approach to this challenging neonatal congenital abnormality.
Keywords: esophageal atresia; tracheoesophageal fistula; thoracoscopy